Microstructural and chemical analysis of nanoscale particles in rapidly solidified Al-V-Fe - Humphreys, E; Warren, P; Cerezo, A; Smith, G (1999)
This paper outlines a combined transmission electron microscope and atom probe investigation of rapidly solidified Al94V4Fe2-(Si) alloys which have been produced by melt spinning. In particular, the effect of silicon additions to the melt has been investigated. The microstructures produced consist of a high volume fraction of nanoscale particles, icosahedral and amorphous, embedded in the fee aluminium matrix. Addition of Si promotes the formation of amorphous rather than quasicrystalline particles. 3-dimensional atom probe results show that both quasicrystalline and amorphous particles are strongly enriched in all of the solute elements (V, Fe, Si). Evidence of solute redistribution during dissolution and coarsening of the particles has also been observed. (C) 1999 Elsevier Science S.A. All rights reserved.